Plant Disease Diagnostic Capabilities in Venezuela: Implications for Food Security - Marys, Edgloris; Rosales, Ligia Carolina (Frontiers in Sustainable Food Systems, 2021)
Venezuela is currently experiencing the most severe humanitarian crisis in the Americas of this century, with minimal local food production affecting food security and hence the population’s right to food. Plant disease outbreaks are causing substantial declines in major staple food and cash crop production and impacting rural livelihoods, posing a significant and growing threat to the already complex food insecurity crisis in the country. Nevertheless, phytosanitary services and hence governance of plant pest and diseases were substantially weakened over the last years as a consequence of the collapse of the economy and the substantial deterioration of the Venezuelan public administration. Therefore, most of the pathogens associated with symptoms causing diseases remain unidentified or uncharacterized, and no surveillance or crop protection strategies have been implemented. In this perspective, we address the country’s issues and challenges in diagnosing, monitoring and managing plant diseases in the context of national food insecurity.